PENGGUNAAN BIRTH BALL SEBAGAI METODE PENGURANGAN RASA NYERI PERSALINAN KALA 1 FASE AKTIF - Dyah Triwidiyantari; Fitri Hadiyanti Hasanah; Nabila Kartika Putri (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2022)
The birth process is synonymous with pain. Pain in labor is a physiological process, but the pain causes some mothers to worry that they will not be able to pass the labor process. Fear and anxiety can cause pain, making the uterine muscles stronger and harder. Whereas anxiety that cannot be managed properly can have a negative impact on the health of the mother and fetus. Many attempts have been made to reduce pain in labor, using non-pharmacological methods. This Community Service aims to reduce the intensity of pain in childbirth using birth ball exercises. In this community service, the exercise method uses a birth ball which is carried out directly on the mother in the first stage of the active phase. To find out whether there is a reduction in pain in the mother, it is measured by the NRS (Numeric Rating Scale). The result is a decrease in moderate to mild pain.